Musculoskeletal injections and alternative options : a practical guide to 'what, when and how?' - Bhatia, Maneesh (Boca Raton : CRC Press, 2019)
Musculoskeletal injections for joint or tendon problems are performed commonly and their use, which can result in a marked improvement in acute symptoms as well as delay or postpone surgery, is on the rise. Key features: Provides concise, current and portable information Covers the latest treatment options, supported by scientific evidence and guidelines Discusses alternative injections, non-injection measures and novel treatment modalities Text supported by illustrations and video of injection procedures and physiotherapy Ideal for both the non-specialist seeking an introduction to the subject and the more experienced practitioner This accessible guide helps doctors from various disciplines including orthopaedics, sports medicine, rheumatology, radiology and primary care as well as allied health care professionals understand the indications and local anatomy to safely perform injections with complication avoidance. In addition, the book provides useful information regarding other alternatives including physiotherapy and novel modalities. The content is supported by current evidence, guidelines and companion videos.
Musculoskeletal injections in general / Devendra Mahadevan and Euan Stirling -- Shoulder and elbow injections / Helen Tunnicliffe and Harvinder Pal Singh -- Hand and wrist injections / Sunil Garg -- Hip and knee injections / Ashwin Kulkarni and Kimberly Lammin -- Foot and ankle injections / Bobby M. Siddiqui, Annette Jones, and Maneesh Bhatia -- Image-guided injections in orthopaedics / Sangoh Lee and Raj Bhatt -- Platelet-rich plasma injections / Kevin Ilo and Fazal Ali -- Visco-supplementation injections / Zaid Abual-Rub and Sanjeev Anand -- Prolotherapy / Roger Oldham -- Extracorporeal shock wave therapy / Randeep Aujla and Philippa Turner -- Novel treatments for the management of chronic shoulder, knee and hip joint pain / Sadiq Bhayani.
OCLC-licensed vendor bibliographic record.
Keywords: Injections, Intramuscular; Musculoskeletal system -- Wounds and injuries -- Treatment; MEDICAL / Pharmacology; MEDICAL / General; MEDICAL / Family & General Practice; MEDICAL / Sports Medicine